Kandungan Gizi Jamur Tiram pada Substrat Kayu Sengon dan Klaras Pisang: Nutrition Contents of Oyster Mushroom on Sengon Wood and Banana Leaves Substrates - Azizah, Malika; Sudirman, Lisdar Idwan; Arifin, Sukarya Zaenal; Setianingsih, Ika; Larasati, Afina; Zulfiqri, Aldy Muhammad (Jurnal Sumberdaya Hayati, 2022)
The study was conducted to observe the growth, fruiting body production and nutritional contents of white oyster mushroom (Pleurotussp., wild HS isolate) grown on 300 g of mixed substrate between sengon sawdust (Albizia chinensis) (SGKS) and dried banana leaves or klaras (Musa sp.) and compared with SGKS, the commonly used single substrate. Both substrates were added with 15% bran, 1.5% lime and 1.5% gypsum. The production of mushroom fruiting bodies on mixed substrates was higher than that of single substrate with biological efficiency of 27.24% and 22.00%, respectively. Likewise, the protein content of the mixed substrate was much higher than that of the single substrate, 19.6% and 10.9%, respectively, while the crude fiber and carbohydrate contents were slightly higher in the single substrate, respectively 8.76% and 54 ,37%. Further research needs to be carried out on a mixed substrate of at least 500 g to get a more complete pattern of the production and biological efficiency.